First record of Africactenus Hyatt, 1954 and redescriptions of two poorly known species of Ctenus Walckenaer, 1805 (Araneae, Ctenidae, Cteninae) from India - Sankaran, Pradeep M.; Sebastian, Pothalil A. (Zootaxa, 2018)
The ctenid genus Africactenus Hyatt, 1954 is recorded for the first time from India. Africactenus unumus sp. nov. is described and illustrated based on male specimens. Detailed redescriptions and illustrations of Ctenus cochinensis Gravely, 1931 (both male and female) and Ctenus indicus Gravely, 1931 (only female) are provided and their distribution in India is updated.